التحرش الجنسي في الوسط المدرسي وتأثيره على التفاعل الاجتماعي داخل المدرسة - شقرانة, أم الخير (Changement Social; No 06 (2019): revue change social, 2019)
نتناول من خلال هذه الدراسة ظاهرة التحرش الجنسي، والتأثير الذي تحدثه على عملية التفاعل الاجتماعي دخل الوسط المدرسي، من اجل الكشف عما يحدث داخل الثانويات، حيث تطرقنا إلى التحرش الجنسي من خلال تعريفه، وطرح أشكاله؛ أما التفاعل الاجتماعي فتناولنا فيه تعريفه وشروطه والعمليات الاجتماعية؛ أما بالنسبة للجانب الميداني فقد تمت الدراسة في إحدى ثانويات الجلفة، وقدرت العينة بثلاثين تلميذة، وقد تم الاعتماد على أداة الاستبيان في جمع البيانات وتوصلنا من خلال الدراسة إلى مجموعة من النتائج من بينها أن أكثر أنواع التحرش انتشارا هو التحرش اللفظي وغير اللفظي، وبنسب ضئيلة جدا نجد التحرش الجسدي، وان أغلبية المتحرشين من فئة التلاميذ تليهم فئة العمال وأخيرا الأساتذة، بالنسبة للفرضيات الفرضية الأولى لم تتحقق حيث توجد علاقة طردية ضعيفة بين التحرش الجنسي والتعاون، بالنسبة للفرضية الثانية لم تتحقق حيث وجد أنها توجد علاقة طردية ضعيفة بين التحرش الجنسي والتكيف أما بالنسبة للفرضية الثالثة فتحققت بحيث توجد علاقة طردية متوسطة القوة بين التحرش والصراع. الكلمات المفتاحية: التفاعل الاجتماعي، التحرش الجنسي. this study, we examine the phenomenon of sexual harassment and the impact it has on the process of social interaction in the middle of the school, in order to discover what is happening within the secondary schools, where we discussed sexual harassment through its definition and the introduction of its forms; the social interaction dealt with its definition, The sample was estimated at 30 students, and the questionnaire was used to collect data. The study found that the most common types of harassment were verbal and nonverbal harassment and in very small numbers we find physical harassment, The majority of the harassed students they followed by the class of workers and finally the professors, For hypotheses, the first hypothesis has not been achieved where there is a weak positive relationship between sexual harassment and collaboration, The second hypothesis was not realized, as it was found that there was a weak positive relationship between sexual harassment and adaptation, For the third hypothesis, it was achieved so that there is a moderately strong relationship between harassment and conflict. Keywords: social interaction, sexual harassment.